2004
DOI: 10.1002/cncr.20166
|View full text |Cite
|
Sign up to set email alerts
|

Mature results of a phase III randomized trial of bacillus Calmette–Guerin (BCG) versus observation and BCG plus dacarbazine versus BCG in the adjuvant therapy of American Joint Committee on Cancer Stage I–III melanoma (E1673)

Abstract: BACKGROUND The local and systemic effects of bacillus Calmette–Guerin (BCG) have been known for decades. To investigate the adjuvant effect of BCG on resected American Joint Committee on Cancer (AJCC) Stage I–III melanoma, the Eastern Cooperative Oncology Group conducted a large trial to study the use of BCG alone or a combination of BCG and dacarbazine between 1974 and 1978. METHODS A total of 734 patients were randomized to 4 clinical groups consolidated into 2 cohorts. Cohort I compared BCG with observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 13 publications
0
41
0
1
Order By: Relevance
“…11,12 The adipose tissue of melanoma patients has been found to contain significantly higher amounts of PUFA than that of controls. 9 When mice were inoculated with melanoma cells, those consuming diets high in PUFA formed tumors faster than control mice did.…”
Section: Reduce the Consumption Of Polyunsaturated Fatty Acidsmentioning
confidence: 98%
See 1 more Smart Citation
“…11,12 The adipose tissue of melanoma patients has been found to contain significantly higher amounts of PUFA than that of controls. 9 When mice were inoculated with melanoma cells, those consuming diets high in PUFA formed tumors faster than control mice did.…”
Section: Reduce the Consumption Of Polyunsaturated Fatty Acidsmentioning
confidence: 98%
“…11 No survival benefit for Bacillus Calmette-Guerin (BCG) or BCG plus dacarbazine was seen in a large trial in patients with stages I to III melanoma. 12 Several vaccines for melanoma are in earlier stages of clinical trials, but overall survival data are not available from these trials, and high-dose IFN remains the bestrecognized Food and Drug Administration-approved adjuvant therapy for melanoma in a stage II patient. 13 That the present patient does not have recurrent disease and that his age is not much older than 49 years are encouraging for his possible response to IFN treatment.…”
Section: Medical Oncologymentioning
confidence: 99%
“…A recent article reported long-term follow-up data from an Eastern Cooperative Oncology Group study initiated in the 1970s to examine the value of adjuvant BCG in stages I-III melanoma [53]. In this study, 734 patients were randomly assigned to receive BCG alone, BCG and dacarbazine, or observation; the results projected to 30 years showed no evidence of a survival benefit associated with adjuvant BCG treatment [53]. In contrast, a European cohort study of 542 patients found that prior immunization with vaccinia or BCG was associated with prolonged survival of patients with melanoma [54].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Asymptomatic individuals often still possess an intact immune system, and hence immunotherapy is a viable option. Whilst the principle that the immune system is capable of controlling cancer is well established [38,[42][43][44], it is only in recent years that advances in immunotherapy have begun to show real clinical benefit [30,45]. Although this is attractive, pitfalls still exist, since it is important to identify patients with fully active immune systems to give them both the optimal chance of mounting a meaningful response and also to avoid subjecting them to treatments with a low probability of success.…”
Section: Box 1 Prostate Cancermentioning
confidence: 99%
“…late stage data with very recent failures in a large Phase III melanoma trial [101]. It is interesting to note that this worldwide trial was randomized against bacillus Calmette-Guerin (BCG), which is known to have immunological activity although its direct clinical effect in melanoma is variable [30,31]. Similarly, Melacine ® failed to show significant efficacy in a randomized trial [32], although further analysis demonstrated that patients with either the HLA-A2 or HLA-C3 class I alleles did show a survival benefit [33].…”
Section: Box 1 Prostate Cancermentioning
confidence: 99%